Effect of different synchronization methods on superovulatory response in cattle - RAWAT, A K; KUMAR, SURESH; SAXENA, M X; MAURYA, S N; SINGH, VIJAY (The Indian Journal of Animal Reproduction, 2023)
The present experiment was designed to evah.;ate different methods of estrus synchronization on superovulatory response in cattle. Embryo donor animals were divided into three groups depending on themethodsofestrussynchronization (i) natural estrus (G-1) (ii) estrus induced with two injections of dinoprost tromethamin (G-11) and (iii) estrus induced by use of buserelin acetate and dinorprost tromethamin (G-lll). All the groups were superovulated using FSH-P @400mg/animal. The effect of estrus synchronization on superovulatory response was measured in terms of mean ovulation rate, number of anovulatory follicles, viable embryos and total ova/ embryos recovered. Blood plasma progesterone concentration was also measured on different days of estrous cycle in the three groups. Results indicated that there was no effect of the method used for estrus synchronization on ·superovulatory response in cattle. Blood plasma progesterone profile did not differ (P=0.05) in the animais of different groups.